Assessment of electricity use for water supply systems in Hatay Province, Vietnam - Bui Phuong Nam; Babel, Mukand Singh; Gupta, Ashim Das; Clemente, Roberto S.; Sutat Weesakul; Electricity of Vietnam (EVN); AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2007)
Water and energy are two highly interconnected sectors and therefore it is good practice to manage them together rather than in isolation. Many research advised that we could save energy, if we save water. In Vietnam, water and energy are currently under severe stress from widespread overuse and pollution caused by the combination of population growth, increased economic activities and inadequate management policies. Hatay is a Red River delta province, bordering with the capital city, Hanoi. Hatay has many favorable conditions for the development of agriculture, industry, tourism and services. It is also one of the provinces in the country having very developed systems of transportation, telecommunication, power and water supply, etc. The main objective of the present study is to analyze the energy intensity of water supply pumps and the relation between water used and electricity required for water supply systems. The study considers three sectors of water use namely Urban, Agricultural and Industrial sectors of Hatay province, Vietnam. Two systems for the urban sector; three systems for the agricultural sector; and eight systems for the industrial sectors are selected for study. The results show that the electricity intensity based on water use was lowest in the agricultural water supply (0.085kWh/m3-0.137kWh/m3) followed by the urban water supply (0.54kWh/m3 - 0.55kWh/m3) and highest in the industrial water supply (0.78kWh/m3- 0.85kWh/m3). Moreover, it is very low in surface water pump systems and high in groundwater sources. The water-use efficiency and benefit-cost analysis are used as a basis of recommendation to the responsible organization for achieving lower electricity intensity.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Water Engineering and Management
Thesis (M.Eng.) - Asian Institute of Technology, 2007
Keywords: Municipal water supply -- Evaluation -- Vietnam -- Hatay; Water-supply -- Evaluation -- Vietnam -- Hatay; Electric power consumption -- Evaluation -- Vietnam -- Hatay